Rural libraries implementing walking groups or walking groups plus civic engagement for walkability in rural communities: a comparative effectiveness trial study protocol - Cynthia K Perry; Rebecca Seguin-Fowler; Jay E. Maddock; Noah Lenstra; Nathan F. Dieckmann; Jessica Currier; Elena Andreyeva; Jim Winkle; Stewart G. Trost (BMC, 2023)
Abstract Background Rural residents generally lack adequate physical activity to benefit health and reduce disparities in chronic diseases, such as cardiovascular disease and certain cancers. The Socioecological Model describes physical activity as involving a dynamic and reciprocal interaction between individual, social, and community factors. Community group-based walking programs and civic engagement interventions aimed at enhancing physical activity have been successful in rural communities but have not targeted all three socioecological levels. Public libraries can act as innovative public health partners in rural communities. However, challenges remain because rural libraries often lack the capacity to implement evidence-based health promotion programming. The goals of this study are (1) build the capacity for rural libraries to implement evidence-based health promotion programs, (2) compare changes in physical activity between a group-based walking program and a combined group-based walking and civic engagement program with rural residents, and (3) conduct an implementation evaluation. Methods We will conduct a comparative effectiveness study of a group-based walking (standard approach) versus a group-based walking plus civic engagement program (combined approach) aimed at enhancing walkability to increase physical activity among rural adults. Key mediators between the program effects and change in outcomes will also be identified. Finally, we will evaluate program implementation, conduct a cost effectiveness evaluation, and use a positive deviance analysis to understand experiences of high and low changers on key outcomes. Twenty towns will be matched and randomized to one of the two conditions and our aim is to enroll a total of 350-400 rural residents (15-20 per town). Study outcomes will be assessed at baseline, and 6, 12, and 24 months. Discussion This study will build the capacity of rural libraries to implement evidence-based walking programs as well as other health promotion programs in their communities. The study results will answer questions regarding the relative effectiveness and cost effectiveness of two multilevel physical activity interventions targeting rural communities. We will learn what works and how these multilevel interventions can be implemented in rural populations. Trial Registration ClinicalTrials.gov Identifier: NCT05677906.